Communication skills for medicine - Lloyd, Margaret (Churchill Livingstone, 2009)
Presents a practical account of communication for medical students, backed up with numerous case histories. This book also contains clinical interview. It covers other aspects of communication including how to promote healthy behaviour and the need for the doctor to work as part of the health care team.